The effect of AlB2 addition on MgB2 superconducting bulks. (1st April 2023) - Da Silva, L B S; Serquis, A; Hellstrom, E E; Rodrigues Jr, D
Abstract: Optimization of intrinsic and extrinsic properties of MgB2 superconducting material is extremely important for practical application in cables, wires, and tapes. The main mechanisms used to obtain this optimization are through the synthesis process, improvement in the grain connectivity, densification, pinning, doping, and limiting MgO formation. Many groups around the world use elements such as Ti, Zr, Hf, Al, Mn, Si and others, as dopants. Defects or any other inhomogeneity in the superconducting matrix can improve the flux pinning behavior and, hence, the transport properties. In this work MgB2 superconducting bulks with additions of AlB2 powder were prepared and analyzed in an attempt to enhance the critical current density of MgB2 and to understand the effect of this addition on the intrinsic and extrinsic characteristics of the material. Crystallographic, microstructural, optical, and superconducting characterization were performed and analyzed. AlB2 additions modified the superconducting properties of MgB2 increasing its critical current density and irreversibility field compared to pure MgB2 prepared using the same procedures.